Implementasi Kebijakan Penyediaan Ruang Bagi Pedagang Kaki Lima Di Pasar Loak Dupak Rukun Kota Surabaya - Baihaqi, Muhammad Hanif Baihaqi; Anggraeny Puspaningtyas; Muhammad Roisul Basyar (Jurnal Publik, 2025)
This research aims to analyze the implementation of the policy of providing space for street vendors at the Dupak Rukun Flea market in Surabaya City. This research uses a qualitative method with a descriptive approach. This research was conducted at the Dupak Rukun flea market in Surabaya City. Data sources were obtained through observation, interviews and documentation. The subjects in this research are Satpol PP, PD Pasar Surya, Flea Market Office, Community. The results of the analysis show that the implementation of the policy of providing space for street vendors (PKL) at the Dupak Rukun Flea Market has led to order and justice, although not yet fully ideal due to limited facilities. The target group, the street vendors, showed a cooperative attitude and were willing to follow the relocation rules. Implementing organizations such as Satpol PP, PD Pasar Surya, and market managers work in a coordinated manner in the policy implementation process. Environmental factors, especially social support and public awareness of order, contributed to the success of this policy, although technical challenges still need to be overcome. Periodic evaluation of the policy, improved communication with street vendors, agency coordination, and continued environmental support are recommended.